Spook street - Herron, Mick (Herron, Mick. Slough House novel., 2017)
"What happens when an old spook starts to lose his mind? Do the Services have a retirement home for people who know too many secrets but don't remember they're secrets? Or does someone come to take care of the senile spy for good? These are the questionsRiver Cartwright must ask himself as his grandfather--David Cartwright, a Cold War-era operative--starts to forget to wear pants, and starts believing everyone in his life is someone sent by Services to watch him. However, River has other things to worryabout. A bomb goes off in the middle of a flash mob performance in a busy shopping center and kills forty innocent civilians. The agents of Slough House have to figure out who is behind this act of terror before the situation escalates"--